Promoting Students about Sustainable Development in Primary School Science - Nuangchalerm, Prasart; Matchimo, Puchong; Polyiem, Titiworada (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2024)
It is imperative that notions of sustainable development be incorporated into the teaching that is provided in elementary schools in order to cultivate a generation that is capable of comprehending sustainable practices and actively participating in them. This article investigates how teaching science in elementary schools might contribute to the promotion of sustainable development. It studies the significance of implementing sustainable development ideas into scientific curricula and classroom activities, such as environmental awareness, resource conservation, and social responsibility. The purpose of this work is to show the benefits of incorporating teaching about sustainable development into primary school science In addition, it highlights the significance of sustainable science in primary school, which enable students to become active contributors to the development of sustainable practices.